Shoe insole for eccentric activities on daily application prevents muscular damage and improves fasting blood glucose - Abdullah, Ahmad; Kusuma, Herdianty; Asnar, Elyana; Purwanto, Bambang (Folia Medica Indonesiana, 2017)
The eccentric contraction has been proven to improve Glut-1 expression in muscle and fasting glucose levels in mice. The same eccentric contraction occurs in human being when walking or running while wearing high heels. Innovation on the eccentric contraction with high heels can be done by using a specific shoe insole. The design of the rear insole is made thicker than the front. The purpose of this study was to determine the effects of insole use specified for eccentric activities on daily work shoes on the skeletal muscle damage after wearing the specified insole. Skeletal muscle damage was measured based on sTnI level. This was experimental study with pretest-posttest design. The subjects involved were non-diabetic woman workers in Faculty of Medicine of Universitas Airlangga, and were divided into two groups. Each group represented group members who wore 5-degree and 10-degree insoles respectively. The angle used for the shoe insoles were 5° and 10° respectively. These insoles were worn on weekdays for one week. Blood was taken one day after the subjects stop wearing the insoles. Data results showed that the levels of fasting blood glucose (FBG) of subjects who wore the 10-degree insole had a value of p<0.05. The use of insole lead to decreased levels of fasting blood glucose (FBG). This study found that the sTnI levels in the 5-degree and 10-degree insole groups had no significant effect on troponin I skeletal muscle levels before and after treatment.